Study of polymer coating delamination kinetics on zinc modified with zinc oxide of different morphologies. Issue 4 (6th February 2014) - Iqbal, D.; Moirangthem, R. Singh; Bashir, A.; Erbe, A.
<x xml:space="preserve">Abstract</x> Industrially prepared materials surfaces often possess complex morphologies and topographies. Using rough model interfaces, the effect of the surface morphology on the delamination of a polymer coating from zinc surfaces is investigated in this work. Zinc oxide particles of different shapes with characteristic dimensions ∼1 µm were deposited on zinc surfaces to serve as model corrosion products with well‐defined morphologies. Surfaces with spherical, rod‐shaped, and twin‐plate‐shaped zinc oxide particles were prepared and characterized by scanning electron microscopy (SEM) as well as X‐ray diffraction (XRD). The surfaces were subsequently coated with poly(vinyl butyral) (PVB) as a model for a weakly bound polymer coating. Scanning Kelvin probe (SKP) measurements were carried out in humid air to study the delamination kinetics. Results were compared to PVB on zinc. While delamination is fastest on zinc without zinc oxide particles, the delamination rate on the particle‐covered surfaces strongly depends on the particle morphology. Delamination rate increases in the order sphere < rod < twin‐plate, with differences by one order of magnitude between fastest and slowest. The differences in delamination rate can be understood based on the surface energies of the terminating surfaces of the particles, and the resulting differences in stability under conditions of zinc oxide dissolution.